2018
DOI: 10.3390/ijms19051349
|View full text |Cite
|
Sign up to set email alerts
|

The Use and Safety of TNF Inhibitors during Pregnancy in Women with Psoriasis: A Review

Abstract: Psoriasis is a chronic immune-mediated inflammatory disease affecting women of childbearing potential. Biologic agents, notably Tumor Necrosis Factor inhibitors (TNFi), are the only current non-contraindicated systemic treatment option during pregnancy. TNFi comprised of complete immunoglobulin G (IgG) antibodies antibodies (adalimumab, golimumab, and infliximab) actively cross the placenta from the second trimester and are detectable in the child up to one year postpartum. Data on safety of TNFi are conflicti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
53
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(59 citation statements)
references
References 50 publications
0
53
0
6
Order By: Relevance
“…However, the authors stated that the diverse fi ndings across disease groups in this study may indicate an association related to the underlying disease activity rather than to agent-specifi c effects [71]. As a general approach, it is recommended that women using anti-TNF- avoid pregnancy and be monitored if they have already become pregnant, but there is no conclusive evidence that adalimumab, infl iximab, etanercept and certolizumab pegol treatments are embryotoxic or teratogenic [59][60][61]. Therefore, it has been reported that the continuation of the treatment according to the risk-benefi t balance should be decided individually in each patient.…”
Section: Pregnancy Course In Patients With Psoriasismentioning
confidence: 87%
See 1 more Smart Citation
“…However, the authors stated that the diverse fi ndings across disease groups in this study may indicate an association related to the underlying disease activity rather than to agent-specifi c effects [71]. As a general approach, it is recommended that women using anti-TNF- avoid pregnancy and be monitored if they have already become pregnant, but there is no conclusive evidence that adalimumab, infl iximab, etanercept and certolizumab pegol treatments are embryotoxic or teratogenic [59][60][61]. Therefore, it has been reported that the continuation of the treatment according to the risk-benefi t balance should be decided individually in each patient.…”
Section: Pregnancy Course In Patients With Psoriasismentioning
confidence: 87%
“…In these periods, the most appropriate treatment after topical agents is broadband or especially narrow band that these anomalies may be biased because they actually refl ect negative outcomes collected by the FDA [66,67]. Data on the safety of anti-TNF- treatments during pregnancy are increasing gradually [59][60][61]. Since these treatments are mostly used in infl ammatory bowel diseases and rheumatoid arthritis, most of the data have been obtained from the literature of gastroenterology and rheumatology [68,69].…”
Section: Pregnancy Course In Patients With Psoriasismentioning
confidence: 99%
“…Unlike others previously mentioned, this biologic lacks the receptor to bind to the Fc placental portion, therefore disabling the possibility of active transport toward fetal circulation. Diverse studies have detected minimal concentrations in neonates whose mothers were treated with this biologic, but it has been inferred that these concentrations might be due to passive transplacental transfer (Johansen et al, ). Likewise, a series of cases regarding 14 pregnant women diagnosed with diverse chronic inflammatory diseases, uninterruptedly treated with certolizumab during pregnancy, demonstrated that neonate concentrations were undetectable or, except one case, minimal (infant/mother plasma ratio of 0.0009) (Mariette et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, it has been observed that when Th17 activity increases above Treg, complications arise, such as preterm labor, preeclampsia, and spontaneous abortions in patients diagnosed with inflammatory diseases such as systemic lupus erythematosus, rheumatoid arthritis, and multiple sclerosis (Figueiredo & Schumacher, 2016). By extrapolation one can infer that psoriasis in itself is a condition that overshadows pregnancy, as its severity is directly related to complications, according to Yang et al, Johansen et al, Odorici et al, and Bröms et al, it can cause spontaneous abortions, preterm labor, and restricted intrauterine growth (Bröms, Haerskjold, Granath, et al, 2018;Figueiredo & Schumacher, 2016;Johansen, Jimenez-Solem, Haerskjold, Sand, & Thomsen, 2018;Odorici et al, 2019;Yang, Chen, Chen, & Lin, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation